2008
DOI: 10.1097/bcr.0b013e3181848192
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Behavioral Perceptions Between Young Adult Burn Survivors and Cross-Informants

Abstract: The purpose of this study is to gain insight into the level of agreement, in terms of personal problems, between burn survivors and an informant with whom they have a close personal relationship. Participants in the study were 72 young adult burn survivors between the ages of 18 and 28 with a mean age of 20.9 +/- 2.6 years. There were 37 males and 35 females in the group. The mean total burn surface area was 55.34 +/- 19.9% with injuries occurring before the age of 18, a minimum of 2 years prior to the study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
(8 reference statements)
0
7
0
Order By: Relevance
“…In other studies, family members attributed more QOL problems for the survivor than the survivors themselves did. 38 Furthermore, since our population was predominantly Hispanic, it would be useful to consider QOL in cohorts with varying ethnicities to determine what other groups use to determine QOL.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, family members attributed more QOL problems for the survivor than the survivors themselves did. 38 Furthermore, since our population was predominantly Hispanic, it would be useful to consider QOL in cohorts with varying ethnicities to determine what other groups use to determine QOL.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have described the Axis I diagnoses , psychological adjustment (Meyer et al, 2004), quality of life (Baker et al, 2008;, suicidal risk (L. , family environment (Rosenberg et al, 2007), and differences in behavioral perception (Russell et al, 2008) among the participants. The study was approved by the University of Texas Medical Branch Institutional Review Board and the sampling method has been previously reported (Meyer et al, 2004).…”
Section: Methodsmentioning
confidence: 96%
“…Where previously attention for psychological adjustment focused on the presence of major psychiatric disorders, it is clear that attention should also be paid to personality development and presence of personality disorders that can interfere with the adjustment and well being of burn trauma survivors. Baker, C., Rosenberg, M., Mossberg, K., Holzer, C., Blakeney, P., Meyer, W., et al (2008). Relationships between the Quality of Life Questionnaire (QLQ)…”
Section: Correlation Between Personality Disorder Diagnosis and Axis mentioning
confidence: 99%
“…Specific behaviors encountered from their social environment include avoidance, staring, and unfriendly conduct 9-13 . Age 8,14 , time post-burn 8,15 , sex 8,16,17 , and injury severity 7,18 have been associated with body image satisfaction and social integration among burn injury survivors.…”
Section: Introductionmentioning
confidence: 99%